The bacterial sulfur cycle in expanding dysoxic and euxinic marine waters - van Vliet, Daan M. (2021)
Dysoxic marine waters (DMW, <1 M oxygen) are currently expanding in volume in the oceans, which has biogeochemical, ecological, and societal consequences on a global scale. In these environments, distinct bacteria drive an active sulfur cycle, which has only recently been recognized for openocean DMW. This review summarizes the current knowledge on these sulfurcycling bacteria. Critical bottlenecks and questions for future research are specifically addressed. Sulfatereducing bacteria (SRB) are core members of DMW. However, their roles are not entirely clear, and they remain largely uncultured. We found support for their remarkable diversity and taxonomic novelty by mining metagenomeassembled genomes from the Black Sea as model ecosystem. We highlight recent insights into the metabolism of key sulfuroxidizing SUP05 and Sulfurimonas bacteria, and discuss the probable involvement of uncultivated SAR324 and BSGSO2 bacteria in sulfur oxidation. Uncultivated Marinimicrobia bacteria with a presumed organoheterotrophic metabolism are abundant in DMW. Like SRB, they may use specific molybdoenzymes to conserve energy from the oxidation, reduction or disproportionation of sulfur cycle intermediates such as S0 and thiosulfate, produced from the oxidation of sulfide. However, this complex network of reactions is yet to be constrained quantitatively. This article is protected by copyright. All rights reserved.